The impact of addition of shiitake on quality characteristics of frankfurter during refrigerated storage. Issue 1 (June 2015) - Pil-Nam, Seong; Park, Kyoung-Mi; Kang, Geun-Ho; Cho, Soo-Hyun; Park, Beom-Young; Van-Ba, Hoa
Abstract: The effect of addition of shiitake levels (0, 0.4, 0.8 and 1.2%) on the quality traits such as physicochemical and microbial properties of frankfurter was studied during refrigerated storage, and its effect was also compared with those produced with 100 ppm NaNO2 . Our results showed that the shiitake incorporation did not cause color and texture defects of frankfurters during storage. The TBARS values of frankfurters produced with shiitake were much lower than those of the control and NaNO2 frankfurters in all storage days. Additionally, the addition of shiitake retarded the growth of aerobic bacteria during storage. Furthermore, the shiitake incorporation significantly ( P  < 0.05) improved the sensory quality at day 1 storage; the higher flavor, taste and acceptability scores were given for the shiitake frankfurters than for the control and NaNO2 frankfurters, probably due to its flavor enhancer and taste-active components. Finally, shiitake with its high bioactivity can be utilized to prevent lipid oxidation and microorganisms growth during storage and improve the sensory characteristics of frankfurters at day 1 storage. It is also suggested that the addition of shiitake powder to meat products is an alternative interesting way to instead of synthetic antioxidants or preservatives. Highlights: The addition of the mushroom did not affect color and texture of frankfurters. The addition of Shiitake significantly inhibited lipid oxidation during storage. The addition of Shiitake significantly retarded the aerobic bacteria growth. Frankfurter made with 0.8% Shiitake had higher antioxidant effect than with NaNO2. The addition of mushroom improved flavor, taste and acceptability of frankfurters.